A new measure of market inefficiency - Christopher R. Stephens; Harald A. Benink; José Luis Gordillo; Juan Pablo Pardo-Guerra (Journal of Risk and Financial Management, 2021)
Financial crises, such as the Great Financial Crisis of 2007-2009 and the COVID-19 Crisis of 2020-2021, lead to high volatility in financial markets and highlight the importance of the debate on the Efficient Markets Hypothesis, a corollary of which is that in an efficient market it should not be possible to systematically make excess returns. In this paper, we discuss a new empirical measure - Excess Trading Returns - that distinguishes between market and trading returns and that can be used to measure inefficiency. We define an Inefficiency Matrix that can provide a complete, empirical characterization of the inefficiencies inherent in a market. We illustrate its use in the context of empirical data from a pair of model markets, where information asymmetries can be clearly understood, and discuss the challenges of applying it to market data from commercial exchanges.
Keywords: 330; behavioural finance; efficient market hypothesis (EMH); excess trading returns; investor's behaviour